Nodal Progression During Radiotherapy Waiting Time: A Case Report From Nasopharyngeal Cancer - Winarni, Tika Wahyu; Rafiq Sulistyo Nugroho (Department of Radiology, Medical Faculty, University of Brawijaya, 2023)
Nasopharyngeal cancer (NPC) is an epithelial cancer that develops from the lining of the nasopharynx. Nasopharyngeal cancer is a highly radiosensitive and chemosensitive type of tumor. Chemoradiotherapy is the treatment backbone for locoregionally advanced NPC; induction chemotherapy followed by chemoradiotherapy is the new standard-of-care therapy in this disease setting. A 49-year-old male patient was diagnosed with nasopharyngeal cancer T2N3Mx. The patient experienced a delay in his radiotherapy treatment for 6 months, and this delayed time and overall treatment time (OTT) affected the development of the patient’s therapy. The patient underwent chemotherapy and radiotherapy procedures and showed good results. The size of the mass reduced, and, based on the result of the biopsy, what remained was non-specific chronic inflammation. Keywords: NPC, progression, radiation therapy, waiting time